Preparation process of carbon steel slag aggregate marine bridge concrete material
Patent Information
- Application Number
- CN202610633775.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-05-09
AI Technical Summary
然而,在实际操作中由于钢渣颗粒表层与CO2反应后生成致密外壳,会显著抑制CO2继续向钢渣颗粒内部的扩散,导致大粒径钢渣颗粒仅表层被碳化,而内部仍然存在相当量的f-CaO、f-MgO,造成钢渣的体积安定性问题仍然存在,从而容易在混凝土服役过程中产生膨胀开裂,尤其是在海洋环境中服役的混凝土桥梁,会造成其中的钢筋在渗入海水中氯离子作用下加速腐蚀,导致桥梁的承载能力下降,寿命缩短
针对传统的碳酸化方式对解决钢渣的体积安定性问题受限较大的问题,本发明先在钢渣的孔隙中负载海藻酸钠,并在此过程中利用钢渣中溶出的钙离子将所述孔隙中的海藻酸钠交联为凝胶产物,此时可以消耗一部分f-CaO,降低了钢渣体积不稳定因素。然后本发明将含有硬脂酸钠的水滑石负载到经过上述处理得到的钢渣颗粒表面后再进行碳化处理,能够有效克服钢渣颗粒表层与CO2反应后生成致密外壳导致内部的f-CaO、f-MgO难以被进一步碳化,造成钢渣的体积安定性问题无法被更好地解决的问题。这是由于:一方面,所述水滑石中的硬脂酸钠在碳化初期与钢渣表面释放的钙离子反应后形成硬脂酸钙,从而在钢渣表面构建憎水区,防止钢渣表面进行碳化反应形成连续的致密外壳,便于二氧化碳进入到钢渣中。另一方面,所述钢渣中的海藻酸钠凝胶产物可吸收水分,便于二氧化碳进入后转化为碳酸根将钢渣中的f-CaO、f-MgO转化为碳酸盐,由于二氧化碳可以更加充分地进入到钢渣内部,从而可以更加彻底地消除钢渣体积安定性不良的问题。再一方面,所述钢渣表面的煅烧水滑石在碳酸化过程中会吸收碳酸根进行层板结构的重建,也会起到固化二氧化碳的作用。另外,采用经过上述处理的钢渣制备混凝土材料时,其中的海藻酸钠凝胶产物可以发挥锁定部分拌和水的作用,这部分水分可在混凝土材料的水化硬化的后期逐渐释放,有助于防止产生的干缩开裂造成混凝土材料强度下降的问题。而所述水滑石能够利用其层板结构吸收氯离子等侵蚀性介质,有助于降低对混凝土材料中钢筋的侵蚀,提高其制造的桥梁等海工结构的服役寿命。
Smart Images

Figure CN122482764B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete material preparation technology, specifically to a preparation process for carbon steel slag aggregate marine bridge concrete material. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Steel slag is a byproduct of steelmaking, producing approximately 100-150 kg of slag for every ton of crude steel produced. The green transformation of the steel industry is urgently needed. As a byproduct of steelmaking, the comprehensive utilization rate of steel slag has long been low. Large-scale stockpiling not only occupies land but also poses environmental risks to surrounding soil and water bodies. Using steel slag to replace natural sand and gravel aggregates or part of the cement in concrete preparation theoretically has significant economic and ecological benefits. However, unlike granulated blast furnace slag, steel slag, due to its high formation temperature and slow cooling process, contains a certain amount of coarsely crystallized, densely structured dead-burned free calcium oxide (calcium oxide). f -CaO), free magnesium oxide ( f These components (MgO) slowly hydrate during the long-term service of hardened concrete, resulting in significant volume expansion, which can easily lead to concrete cracking, strength reduction, and even structural failure. This is because... f - When CaO reacts with water to form Ca(OH)₂, its volume expands by approximately 98%, while f When MgO forms Mg(OH)2, its volume expands by as much as 148%, which can lead to cracking and strength degradation in concrete structures. This "poor stability" is a key issue restricting the application of steel slag in concrete.
[0004] Currently, using carbon dioxide or carbon dioxide-containing industrial waste gas to carbonate steel slag not only helps to dissolve the... f -CaO, f -MgO reduces the potential volume stability issues and can also achieve carbon dioxide absorption and solidification. However, in practice, the dense outer shell formed after the surface of steel slag particles reacts with CO2 significantly inhibits the further diffusion of CO2 into the interior of the steel slag particles. This results in large-diameter steel slag particles being carbonized only on the surface, while a considerable amount of CO2 remains inside. f -CaO, f The presence of -MgO in steel slag still causes volume stability issues, making it prone to expansion and cracking during concrete service. This is especially true for concrete bridges serving in marine environments, where the reinforcing steel is accelerated to corrode under the influence of chloride ions in seawater, leading to a decrease in the bridge's load-bearing capacity and a shortened lifespan. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a preparation process for marine bridge concrete materials using carbon steel slag aggregate, which effectively enhances the degree of carbonation treatment of steel slag and reduces the carbonation content of the steel slag. f -CaO, f The MgO content improves the volume stability of steel slag. Specifically, the technical solution of the present invention is as follows.
[0006] A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) The fine aggregate of steel slag is mixed with sodium alginate solution and then ultrasonically treated. The fine aggregate is then separated, stirred and dried, and sieved to obtain pretreated fine aggregate for later use.
[0007] (2) The modified hydrotalcite powder obtained by calcination is dispersed in sodium stearate aqueous solution to form a dispersion, and then sprayed into the pretreated fine aggregate and stirred evenly. After being sealed in a carbon dioxide atmosphere, it is subjected to carbonation treatment. After completion, it is dried to obtain stabilized steel slag fine aggregate for later use.
[0008] (3) Using cementitious components, stabilized steel slag fine aggregate, silica fume, magnesia fiber and water-reducing agent as raw materials, mix them evenly and then add mixing water and stir evenly to obtain the wall building material.
[0009] Further, in step (1), the ratio of the steel slag fine aggregate to the sodium alginate solution is 1g:30~40mL. Optionally, the mass fraction of the sodium alginate solution is 0.5~1.2%.
[0010] Furthermore, in step (1), the ultrasonic treatment time is 15~25 min.
[0011] Furthermore, in step (1), the particle size of the pretreated fine aggregate is 0.5~1mm.
[0012] Furthermore, in step (1), the drying temperature is 70~85℃ and the time is 1~1.5 hours.
[0013] Further, in step (2), the calcination treatment is carried out at a temperature of 420~470℃ for 65~80 minutes. Optionally, the fineness of the hydrotalcite powder is not less than 400 mesh.
[0014] Further, in step (2), the content of modified hydrotalcite powder in the dispersion is 23~28 g / L. Optionally, the sodium stearate aqueous solution is a saturated solution at 60~70℃.
[0015] Further, in step (2), the ratio of the dispersion to the pretreated fine aggregate is 5~7.5mL:1g.
[0016] Furthermore, in step (2), the carbonization process takes 10 to 12 hours and the temperature is 105 to 115°C.
[0017] Further, in step (3), the proportions of each component in the raw materials are as follows: 140-152 parts by weight of cementitious component, 195-213 parts by weight of stabilized steel slag fine aggregate, 15-20 parts by weight of silica fume, 8-11 parts by weight of magnesia fiber, and 1.8-3.4 parts by weight of water-reducing agent.
[0018] Further, in step (3), the mass ratio of mixing water to cement cementitious components and total silica fume is 0.42~0.46:1.
[0019] Compared with the prior art, the present invention has at least the following beneficial technical effects: To address the limitation of traditional carbonation methods in solving the volume stability problem of steel slag, this invention first loads sodium alginate into the pores of the steel slag. During this process, calcium ions dissolved from the steel slag crosslink the sodium alginate in the pores into a gel product, which can consume a portion of the calcium ions in the slag. f -CaO reduces the volumetric instability factors of steel slag. Then, this invention loads hydrotalcite containing sodium stearate onto the surface of the steel slag particles obtained after the above treatment before carbonization, effectively overcoming the problem of a dense outer shell formed after the surface of the steel slag particles reacts with CO2, which leads to internal instability. f -CaO, f -MgO is difficult to further carbonize, which makes it difficult to better solve the volume stability problem of steel slag. This is because: on the one hand, the sodium stearate in the hydrotalcite reacts with the calcium ions released on the surface of the steel slag in the early stage of carbonization to form calcium stearate, thereby constructing a hydrophobic zone on the surface of the steel slag, preventing the formation of a continuous dense shell through carbonization, and facilitating the entry of carbon dioxide into the steel slag. On the other hand, the sodium alginate gel product in the steel slag can absorb moisture, facilitating the conversion of carbon dioxide into carbonate ions after entry, thus preventing the formation of a continuous dense shell on the surface of the steel slag. f -CaO, f-MgO is converted into carbonates, allowing carbon dioxide to penetrate the steel slag more fully, thus more thoroughly eliminating the problem of poor volume stability in the steel slag. Furthermore, the calcined hydrotalcite on the surface of the steel slag absorbs carbonate ions during carbonation, rebuilding the lamellar structure and also solidifying carbon dioxide. Additionally, when using the treated steel slag to prepare concrete, the sodium alginate gel product can lock in some of the mixing water. This water is gradually released during the later stages of hydration and hardening of the concrete, helping to prevent shrinkage cracking that reduces the strength of the concrete. The hydrotalcite, with its lamellar structure, can absorb corrosive media such as chloride ions, helping to reduce corrosion of the reinforcing steel in the concrete and extending the service life of bridges and other marine structures constructed from it. Attached Figure Description
[0020] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Hereinafter, embodiments of the invention will be described in detail with reference to the accompanying drawings, wherein: Figure 1 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 1 below.
[0021] Figure 2 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 2 below.
[0022] Figure 3 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 3 below.
[0023] Figure 4 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 4 below.
[0024] Figure 5 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 5 below.
[0025] Figure 6 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 6 below.
[0026] Figure 7 The image shows a sample of stabilized steel slag fine aggregate prepared in Example 7 below. Detailed Implementation
[0027] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments.
[0028] Example 1 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Steel slag fine aggregate is mixed with sodium alginate aqueous solution with a mass fraction of 0.8% at a ratio of 1g:35mL and ultrasonically treated for 15min. Then, the fine aggregate is filtered out and heated to 75℃ and stirred and dried for 1 hour. Then, it is sieved using a sieve and the particles with a particle size distribution of 0.5~1mm are used as pretreated fine aggregate for later use.
[0029] (2) Take magnesium aluminum carbonate type hydrotalcite powder (Mg6Al2(OH) with a fineness of 400 mesh) 16 Calcination treatment was performed by heating CO3·4H2O to 450℃ and holding for 70 minutes. After completion, the mixture was cooled to room temperature to obtain modified hydrotalcite powder. The calcined hydrotalcite powder was then added to a saturated aqueous solution of sodium stearate at 60℃ and stirred until homogeneous to obtain a dispersion. The modified hydrotalcite powder content was 25 g / L. The dispersion was then sprayed onto the pretreated fine aggregate at a ratio of 6.5 mL: 1 g and stirred until homogeneous. The resulting wet material was then placed in a carbonation chamber filled with carbon dioxide atmosphere, sealed, and heated to 110℃ for 11 hours for carbonation treatment. After completion, the mixture was cooled to room temperature and then dried to remove residual moisture, yielding stabilized steel slag fine aggregate (e.g., ...). Figure 1 (As shown), for later use.
[0030] (3) Take the following raw materials in the following proportions: 145 parts by weight of cement powder (PO42.5), 207 parts by weight of stabilized steel slag fine aggregate in this embodiment, 18 parts by weight of silica fume, 10 parts by weight of magnesium hydroxide fiber powder, and 2.5 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 73 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0031] Performance Testing: 1. The wall building material prepared in this embodiment was poured into a mold, hardened, demolded, and then placed in a standard curing chamber for 96 days to obtain the test specimen. The compressive strength of the test specimen was then tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GBT 50081-2019). 2. The "Chloride Ion Penetration Resistance Test" of the wall building material in this embodiment was conducted according to the "Standard for Test Methods of Long-Term Performance and Durability of Concrete" (GBT 50082-2024), and the results are shown in Table 1 below.
[0032] Table 1
[0033] Example 2 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Steel slag fine aggregate is mixed with sodium alginate aqueous solution with a mass fraction of 0.5% at a ratio of 1g:40mL and ultrasonically treated for 20min. Then, the fine aggregate is filtered out and heated to 70℃ and stirred and dried for 1.5 hours. Then, it is sieved using a sieve and the particles with a particle size distribution of 0.5~1mm are used as pretreated fine aggregate for later use.
[0034] (2) Take magnesium aluminum carbonate type hydrotalcite powder (Mg6Al2(OH) with a fineness of 450 mesh) 16 Calcination treatment was performed by heating CO3·4H2O to 420℃ and holding for 80 minutes. After completion, the mixture was cooled to room temperature to obtain modified hydrotalcite powder. The calcined hydrotalcite powder was then added to a saturated aqueous solution of sodium stearate at 60℃ and stirred until homogeneous to obtain a dispersion. The content of the modified hydrotalcite powder was 23 g / L. The dispersion was then sprayed onto the pretreated fine aggregate at a ratio of 7.5 mL: 1 g and stirred until homogeneous. The resulting wet material was then placed in a carbonation chamber filled with carbon dioxide atmosphere, sealed, and heated to 105℃ for 12 hours for carbonation treatment. After completion, the mixture was cooled to room temperature and then dried to remove residual moisture, yielding stabilized steel slag fine aggregate (e.g., Figure 2 (As shown), for later use.
[0035] (3) Take the following raw materials in the following proportions: 152 parts by weight of cement powder (PO42.5), 213 parts by weight of stabilized steel slag fine aggregate in this embodiment, 20 parts by weight of silica fume, 11 parts by weight of magnesium hydroxide fiber powder, and 3.4 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 79.1 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0036] Performance testing: The test specimen made of the wall building material described in this embodiment was subjected to compressive strength testing and "chlorine ion penetration resistance test". The method was the same as in Embodiment 1 above. The test results are shown in Table 2 below.
[0037] Table 2
[0038] Example 3 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Steel slag fine aggregate is mixed with sodium alginate aqueous solution with a mass fraction of 1.2% at a ratio of 1g:30mL and ultrasonically treated for 25min. Then, the fine aggregate is filtered out and heated to 85℃ and stirred and dried for 1 hour. Then, it is sieved using a sieve and the particles with a particle size distribution of 0.5~1mm are used as pretreated fine aggregate for later use.
[0039] (2) Take magnesium aluminum carbonate type hydrotalcite powder (Mg6Al2(OH) with a fineness of 500 mesh) 16 Calcination treatment was performed by heating CO3·4H2O to 470℃ and holding for 65 minutes. After completion, the mixture was cooled to room temperature to obtain modified hydrotalcite powder. The calcined hydrotalcite powder was then added to a saturated aqueous solution of sodium stearate at 70℃ and stirred until homogeneous to obtain a dispersion. The content of the modified hydrotalcite powder was 28 g / L. The dispersion was then sprayed onto the pretreated fine aggregate at a ratio of 5 mL: 1 g and stirred until homogeneous. The resulting wet material was then placed in a carbonation chamber filled with carbon dioxide atmosphere, sealed, and heated to 115℃ for 10 hours for carbonation treatment. After completion, the mixture was cooled to room temperature and then dried to remove residual moisture, yielding stabilized steel slag fine aggregate (e.g., Figure 3 (As shown), for later use.
[0040] (3) Take the following raw materials in the following proportions: 140 parts by weight of cement powder (PO42.5), 195 parts by weight of stabilized steel slag fine aggregate in this embodiment, 15 parts by weight of silica fume, 8 parts by weight of magnesium hydroxide fiber powder, and 1.8 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 65.1 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0041] Performance testing: The test specimen made of the wall building material described in this embodiment was subjected to compressive strength testing and "chlorine ion penetration resistance test". The method was the same as in Embodiment 1 above. The test results are shown in Table 3 below.
[0042] Table 3
[0043] Example 4 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Steel slag fine aggregate with a particle size distribution of 0.5~1mm was placed in a carbonation box filled with carbon dioxide atmosphere and water vapor, sealed, heated to 110℃ and held for 11 hours for carbonation treatment, cooled to room temperature after completion, and then dried to remove residual moisture to obtain stabilized steel slag fine aggregate (e.g. Figure 4 (As shown), for later use.
[0044] (2) Take the following raw materials in the following proportions: 145 parts by weight of cement powder (PO42.5), 207 parts by weight of stabilized steel slag fine aggregate in this embodiment, 18 parts by weight of silica fume, 10 parts by weight of magnesium hydroxide fiber powder, and 2.5 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 73 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0045] Performance testing: The test specimen made of the wall building material described in this embodiment was subjected to compressive strength testing and "chlorine ion penetration resistance test". The method was the same as in Embodiment 1 above. The test results are shown in Table 4 below.
[0046] Table 4
[0047] Example 5 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Take magnesium aluminum carbonate type hydrotalcite powder (Mg6Al2(OH) with a fineness of 500 mesh) 16 Calcination treatment was performed by heating CO3·4H2O to 470℃ and holding for 65 minutes. After completion, the mixture was cooled to room temperature to obtain modified hydrotalcite powder. The calcined hydrotalcite powder was then added to a saturated aqueous solution of sodium stearate at 70℃ and stirred until homogeneous to obtain a dispersion. The content of the modified hydrotalcite powder was 28 g / L. The dispersion was then sprayed onto fine steel slag aggregate with a particle size distribution of 0.5~1 mm at a ratio of 5 mL:1 g and stirred until homogeneous. The resulting wet material was then placed in a carbonation chamber filled with carbon dioxide atmosphere, sealed, and heated to 115℃ for 10 hours for carbonation treatment. After completion, the mixture was cooled to room temperature and then dried to remove residual moisture, yielding stabilized fine steel slag aggregate (e.g., [missing information - likely a specific type of aggregate]). Figure 5 (As shown), for later use.
[0048] (2) Take the following raw materials in the following proportions: 140 parts by weight of cement powder (PO42.5), 195 parts by weight of stabilized steel slag fine aggregate in this embodiment, 15 parts by weight of silica fume, 8 parts by weight of magnesium hydroxide fiber powder, and 1.8 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 65.1 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0049] Performance testing: The test specimens made of the wall building materials described in this embodiment were subjected to compressive strength testing and chloride ion penetration resistance testing. The methods were the same as those in Embodiment 1 above, and the test results are shown in Table 5 below.
[0050] Table 5
[0051] Example 6 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Steel slag fine aggregate is mixed with sodium alginate aqueous solution with a mass fraction of 0.5% at a ratio of 1g:40mL and ultrasonically treated for 20min. Then, the fine aggregate is filtered out and heated to 70℃ and stirred and dried for 1.5 hours. Then, it is sieved using a sieve and the particles with a particle size distribution of 0.5~1mm are used as pretreated fine aggregate for later use.
[0052] (2) Take magnesium aluminum carbonate type hydrotalcite powder (Mg6Al2(OH) with a fineness of 450 mesh) 16 Calcination treatment was performed by heating CO3·4H2O to 420℃ and holding for 80 minutes. After completion, the mixture was cooled to room temperature to obtain modified hydrotalcite powder. The calcined hydrotalcite powder was then added to a 60℃ aqueous solution and stirred until homogeneous to obtain a dispersion. The content of the modified hydrotalcite powder was 23 g / L. The dispersion was then sprayed onto the pretreated fine aggregate at a ratio of 7.5 mL: 1 g and stirred until homogeneous. The resulting wet material was then placed in a carbonation chamber filled with carbon dioxide atmosphere, sealed, and heated to 105℃ for 12 hours for carbonation treatment. After completion, the mixture was cooled to room temperature and then dried to remove residual moisture, yielding stabilized steel slag fine aggregate (e.g., [missing information]). Figure 6 (As shown), for later use.
[0053] (3) Take the following raw materials in the following proportions: 152 parts by weight of cement powder (PO42.5), 213 parts by weight of stabilized steel slag fine aggregate in this embodiment, 20 parts by weight of silica fume, 11 parts by weight of magnesium hydroxide fiber powder, and 3.4 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 79.1 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0054] Performance testing: The test specimen made of the wall building material described in this embodiment was subjected to compressive strength testing and "chlorine ion penetration resistance test". The method was the same as in Embodiment 1 above. The test results are shown in Table 6 below.
[0055] Table 6
[0056] Example 7 A preparation process for a carbon steel slag aggregate marine bridge concrete material includes the following steps: (1) Steel slag fine aggregate is mixed with sodium alginate aqueous solution with a mass fraction of 0.8% at a ratio of 1g:35mL and ultrasonically treated for 15min. Then, the fine aggregate is filtered out and heated to 75℃ and stirred and dried for 1 hour. Then, it is sieved using a sieve and the particles with a particle size distribution of 0.5~1mm are used as pretreated fine aggregate for later use.
[0057] (2) A saturated aqueous solution of sodium stearate at 60°C was sprayed onto the pretreated fine aggregate at a ratio of 6.5 mL: 1 g and stirred evenly. The resulting wet material was then placed in a carbonation chamber filled with carbon dioxide atmosphere, sealed, and heated to 110°C for 11 hours for carbonation treatment. After completion, the material was cooled to room temperature and then dried to remove residual moisture, resulting in stabilized steel slag fine aggregate (e.g. Figure 7 (As shown), for later use.
[0058] (3) Take the following raw materials in the following proportions: 145 parts by weight of cement powder (PO42.5), 207 parts by weight of stabilized steel slag fine aggregate in this embodiment, 18 parts by weight of silica fume, 10 parts by weight of magnesium hydroxide fiber powder, and 2.5 parts by weight of polycarboxylate superplasticizer. Add the above components to a mixer and mechanically mix for 3 minutes. Then add 73 parts by weight of mixing water and continue mixing for 2 minutes to obtain the wall building material.
[0059] Performance testing: The test specimen made of the wall building material described in this embodiment was subjected to compressive strength testing and "chlorine ion penetration resistance test". The method was the same as in Embodiment 1 above. The test results are shown in Table 7 below.
[0060] Table 7
[0061] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A preparation process for carbon steel slag aggregate marine bridge concrete material, characterized in that, Includes the following steps: (1) The fine aggregate of steel slag is mixed with sodium alginate solution and then ultrasonically treated. The fine aggregate is then separated, stirred and dried, and sieved to obtain pretreated fine aggregate for later use. (2) The modified hydrotalcite powder obtained by calcination at 420~470℃ for 65~80min is dispersed in sodium stearate aqueous solution to form a dispersion, and then sprayed into the pretreated fine aggregate and stirred evenly. After being sealed in a carbon dioxide atmosphere, it is carbonized and dried to obtain stabilized steel slag fine aggregate for later use. (3) Take the following proportions of raw materials: 140-152 parts by weight of cementitious component, 195-213 parts by weight of stabilized steel slag fine aggregate, 15-20 parts by weight of silica fume, 8-11 parts by weight of magnesium hydroxide fiber, and 1.8-3.4 parts by weight of water-reducing agent; mix them evenly and then add mixing water and stir evenly to obtain the marine bridge concrete material.
2. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (1), the particle size of the pretreated fine aggregate is 0.5~1mm.
3. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (1), the ratio of the steel slag fine aggregate to the sodium alginate solution is 1g:30~40mL.
4. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (1), the mass fraction of the sodium alginate solution is 0.5-1.2%.
5. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (1), the ultrasonic treatment time is 15~25 min.
6. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (1), the drying temperature is 70~85℃ and the time is 1~1.5 hours.
7. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (2), the fineness of the hydrotalcite powder is not less than 400 mesh.
8. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (2), the content of modified hydrotalcite powder in the dispersion is 23~28 g / L.
9. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (2), the sodium stearate aqueous solution is a saturated solution at 60~70℃.
10. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (2), the ratio of the dispersion to the pretreated fine aggregate is 5~7.5mL:1g.
11. The preparation process of carbon steel slag aggregate marine bridge concrete material according to claim 1, characterized in that, In step (2), the carbonization process takes 10 to 12 hours and the temperature is 105 to 115°C.
12. The preparation process of carbon steel slag aggregate marine bridge concrete material according to any one of claims 1-11, characterized in that, In step (3), the mass ratio of mixing water to cement binder and silica fume is 0.42 to 0.46:1.
Citation Information
Patent Citations
Preparation method and application of steel slag aggregate carbon sequestration marine concrete material
CN121494373A
Preparation process of carbon reduction type steel slag aggregate 3D printing cement-based material
CN121554245A